Poppy Harmon and the backstabbing bachelor - Hollis, Lee (Hollis, Lee. Desert Flowers mysteries, 2022)
"While sidekick Matt Flowers shoots a film abroad, Poppy dusts off her own acting chops to break up a Gen Z crime ring targeting seniors in Palm Springs. Tanya Cook and her gal pals have been swindling susceptible residents for all they're worth -- until the gang meets Poppy undercover ... Poppy's already sweating over a menacing mystery stalker when a shocking death proves she's in serious danger. As suspicions fall once again on Tanya, finding answers may mean pulling off the most challenging performance of her career"--